ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PERUSAHAAN DI BURSA EFEK INDONESIA - B51112068, Nelly Jayanti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Corporate Social Responsibility is a form of corporate responsibility in improving social disparities and environmental damage that occurs due to the operational activities of a company. While profitability is the ability of the company in generating profits so that it is able to increase the shareholder value of the company. With high profitability, will give more opportunities to management in expressing and do his the CSR programs. This research aims to test the influence of Corporate Social Responsibility (CSR) towards the profitability of consumer goods companies registered in BEI. Profitability ratio used is the Net Profit Margin (NPM) and the Return On Equity (ROE). This research use Corporate Social Responsibility Disclosure Index (CSRI) as a measure of disclosure of CSR, based on indicators that are presupposed by the Global Reporting Initiatives (GRI). Data collection using a purposive sampling method against consumer goods registered in BEI 2013 up to 2015. As many as 29 companies that qualify as research samples. After the test is done by using simple linear regression analysis method the research indicates that the results of the CSR effect significantly to consumer goods company NPM, but not significant effect against ROE company of consumer goods registered in BEI. Keywords: Corporate Social Responsibility (CSR), profitability, and Corporate Social Responsibility index (CSRI).